Environmental, health and humanity issues in the down Danubian region : multidisciplinary approaches : proceedings of the 9th International Symposium on Interdisciplinary Regional Research, 21-22 June 2007, University of Novi Sad - Mihailovic, Dragutin T.; Vojinović-Miloradov, Mirjana (World Scientific, 2009)
In order to preserve this world for future generations, we must strive for sustainable development - a development that meets the needs of the present generation without compromising options and resources for future generations to meet their own needs. However, some scientists suspect that recent large floods, heat waves and drought in Central Europe and the Down Danubian region are indicators of more severe hazardous events in the future. Increased pollution in the atmosphere is causing gradual increase of the temperature. The environment is becoming increasingly endangered, especially as hum.